Faktor penentu niat terhadap perkongsian maklumat mangsa banjir Rantau Panjang, Kelantan dari perspektif teori kognitif social - Nurzawani, Mohamad Zani (2015)
Information sharing is important to help reduce the uncertainty while waiting for rescue. Through information sharing it can help save lives and properties; minimize the effects of natural disaster; and help to rebuild victim’s confidence. Despite the importance of information sharing, very few studies focused their attention towards understanding the factors that determine the intention to share information especially among flood victims. This research adopts Social cognitive theory as the underlying theory that builds up the conceptual model for this study. The data was collected using a survey technique. Flood victims from Rantau Panjang, Kelantan were selected as respondents. A total of 108 respondents responded to the questionnaire. Smart PLS 3.0 software was used to analyze the data. The research findings showed that information sharing intention among flood victim is influenced by three factors: self-efficacy, social support, and social recognition. Meanwhile reciprocity has been found not significant. Theoretically, this study contributes to the understanding of the determinants factors that influence information sharing intention among flood victims. It also extends the use of Social cognitive theory within the domain of information sharing during disaster. Practically, this study has outlined a number of recommendations to help promote information sharing behavior during disaster. This study proposed awareness programs such as lectures, advertisement, and campaigns to promotes information sharing among wider public. In addition, this study also suggested for a database development to store shared information in order to better facilitate disaster management.